2016
DOI: 10.1111/beer.12132
|View full text |Cite
|
Sign up to set email alerts
|

Corporate recidivism in emerging economies

Abstract: Prior research on corporate misconduct pays extensive attention to single misconduct behaviors. However, little research has addressed recidivism -the repeated behaviors of corporate misconduct. Based on institutional theory and using the context of emerging economies where recidivism plays a considerable role, we propose the path dependency of corporate recidivism and suggest that three influential factors exist: internal preconditioning, inter-organizational imitation, and the prevailing external evaluation.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 64 publications
(96 reference statements)
0
13
0
Order By: Relevance
“…Empirical studies show that peer misconduct, including antisocial and dishonest behavior, is positively associated with misconduct occurring among observers (Robinson and O'Leary-Kelly, 1998;McCabe et al, 2006). Zheng and Chun (2017) show that interorganizational imitation plays a considerable role in corporate recidivism in Chinese economies. O'Fallon and Butterfield (2012) find that, through a vicarious learning process, witnessing unethical peer behavior directly affects the likelihood of an observer behaving unethically.…”
Section: Repeated Ethical Violationmentioning
confidence: 96%
See 2 more Smart Citations
“…Empirical studies show that peer misconduct, including antisocial and dishonest behavior, is positively associated with misconduct occurring among observers (Robinson and O'Leary-Kelly, 1998;McCabe et al, 2006). Zheng and Chun (2017) show that interorganizational imitation plays a considerable role in corporate recidivism in Chinese economies. O'Fallon and Butterfield (2012) find that, through a vicarious learning process, witnessing unethical peer behavior directly affects the likelihood of an observer behaving unethically.…”
Section: Repeated Ethical Violationmentioning
confidence: 96%
“…Following the recent global financial crisis, disclosing information on probable portfolio losses has become an important issue for salespeople to consider in their sales and service behavior. Investigated information disclosure and offense, Zheng and Chun (2017) found that unqualified disclosure indicating some degree of financial problems is more likely to become recidivism. Cooper et al (2014) found that unethical behavior is negatively related to robust ethical code enforcement in an organization.…”
Section: Observer Characteristics (Experience)mentioning
confidence: 99%
See 1 more Smart Citation
“…For example, recent scholarship documents variations in both CSR conceptions (CSR thinking) and CSR applications (CSR doing) in developing countries (e.g., Jamali and Karam, 2016); the endogenous forms of CSR activities of small-to-medium size enterprises (e.g., Karam and Jamali, 2015); the culturally-based socially responsible or irresponsible practices of local companies within specific nations framed in the context of traditions (e.g., Balasubramanian, Kimber & Siemensma, 2005;Husted, 2014;Zheng and Chun, 2016); and the distinct CSR excursions of developing country multinational enterprises as compared to their global counterparts (e.g., Doh, Husted, & Yang, 2016;Preuss, Barkeryeyer & Glavas, 2016). Our paper contributes to this growing stream of literature by fleshing out a yet unexplored dimension of variation relating to the complex translation of the institutional logics surrounding CSR in developing countries through the interplay of global assumptive logics and their local endogenous adaptations/iterations.…”
Section: Introductionmentioning
confidence: 99%
“…The third egoistic motive (E3), that is, tax write off as a CSR motive, is positioned in a separate cluster (C‐III) and perceived by consumers as the most distant in comparison to other motives. Based on the statement of Hoi, Wu, and Zhang () that companies with excessive socially irresponsible activities are more aggressive in avoiding taxes, it can be concluded that this motive is rather attributed to companies’ irresponsibility, as well as recidivism in misconduct, as a phenomenon present in post‐socialist countries (Zheng & Chun, ), and not related to CSR programs and motives.…”
Section: Resultsmentioning
confidence: 99%